2014
DOI: 10.1109/jssc.2014.2314439
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Element Phased-Array System With Simultaneous Spatial- and Frequency-Domain Filtering at the Antenna Inputs

Abstract: -To reject strong interference in excess of 0 dBm, a 4-element LO-phase shifting phased-array receiver with 8-phase passive mixers terminated by baseband capacitors is presented. The passive mixers up-convert both the spatial and frequency domain filtering from baseband to RF, hence realizing blocker suppression directly at the antenna inputs. A comprehensive mathematical model provides a set of closed-form equations describing the spatial and frequency domain filtering including imperfections. A prototype is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Recent research has shown that N-path filters are promising candidates to realize tunable band-pass filters [2]- [12] and also simultaneous frequency and spatial domain filtering [13], [14]. Although the concept dates back to the 1960s [15], [16], only with the advent of nanometer CMOS technologies can such filters now operate at low GHz RF frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that N-path filters are promising candidates to realize tunable band-pass filters [2]- [12] and also simultaneous frequency and spatial domain filtering [13], [14]. Although the concept dates back to the 1960s [15], [16], only with the advent of nanometer CMOS technologies can such filters now operate at low GHz RF frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the linearity of passive mixers realized with MOS switches can be very good, and blockers in the order of 0 dBm can be handled provided the switches have sufficient overdrive voltage. As switches and capacitors scale well with CMOS downscaling, the technique can benefit from process scaling (see for instance [14] which compares a 65 nm and 28 nm chip).…”
Section: Introductionmentioning
confidence: 99%
“…N-path filters can not only be used for frequency-domain filtering, but also for spatial domain filtering, i.e. beamforming, as demonstrated in [55,59,[64][65][66]. Especially if implemented at the first node of the receiver, very high compression point and Fig.…”
Section: Discussion and New Application Directionsmentioning
confidence: 99%
“…IIP3 is possible [66]. Another interesting property of N-path filtering is the controllable gain and group delay [67], which was exploited to improve wideband self-interference cancellation for an in-channel full duplex transceiver [68].…”
Section: Discussion and New Application Directionsmentioning
confidence: 99%
“…This is not desirable from a functional point of view due to the physical volume this occupies. These developments resulted in the design of blocker-tolerant receivers without front end filters suitable for wideband wireless applications [137][138][139].…”
Section: Discussion On Possible Improvementsmentioning
confidence: 99%